2018
DOI: 10.1021/acs.jchemed.8b00048
|View full text |Cite
|
Sign up to set email alerts
|

Whether and How Authentic Contexts Using a Virtual Chemistry Lab Support Learning

Abstract: How can we help students develop an understanding of chemistry that integrates conceptual knowledge with the experimental and computational procedures needed to apply chemistry in authentic contexts? The current work describes ChemVLab+, a set of online chemistry activities that were developed using promising design principles from chemistry education and learning science research: setting instruction in authentic contexts, connecting concepts with science practices, linking multiple representations, and using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 40 publications
1
73
1
Order By: Relevance
“…At the same time, a great variety of digital educational objects including VLs are available in various repositories, to be used as a substitute or alongside hands on experiments with physical instruments. VLs provide opportunities when physical laboratories are not available or practical (Davenport 2018 ). Arduino experiments may bridge the gap of virtual vs. physical instrumentation as being a tool to conduct experiments with physical instruments and substances in a mixed virtual-physical learning environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, a great variety of digital educational objects including VLs are available in various repositories, to be used as a substitute or alongside hands on experiments with physical instruments. VLs provide opportunities when physical laboratories are not available or practical (Davenport 2018 ). Arduino experiments may bridge the gap of virtual vs. physical instrumentation as being a tool to conduct experiments with physical instruments and substances in a mixed virtual-physical learning environment.…”
Section: Discussionmentioning
confidence: 99%
“…A mixed virtual-physical learning environment has to facilitate the alternative learning paths, and it is appropriate for educational systems, where various barriers (e.g. limited infrastructure) confront with hands-on experimentation in real lab (Davenport, 2018;Tatli & Ayas, 2013;Tountoulidis, 2011). Arduino instrumentation is appropriate for this purpose since it can transmit data from sensors to a PC by using inexpensive infrastructure (Grinias et al, 2016) and therefore bridge the gap between virtual learning environment and real instruments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, in recent years the use of software has become ubiquitous in education settings [16][17][18][19][20][21]. It is well known that laboratory equipments are of significant importance in chemistry lab.…”
Section: Resultsmentioning
confidence: 99%
“…Since the initial introductions of the VL concepts, research on the effectiveness of VLs confirmed that properly designed virtual simulation tools can enhance students' learning processes [9], [10]. As a result, VLs have been implemented and/or studied across the wide variety of disciplines, such as life science (e.g., biology) [11], [12], [13], [14], [15], physical sciences (e.g., physics and chemistry) [16], [17], [18], [19], [20], mathematics/computer sciences [21], [22], [23], [24], [25], and engineering [26], [27], [28], [29], [30].…”
Section: Literature Reviewmentioning
confidence: 97%